2020
DOI: 10.3389/fped.2020.00061
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Preterm Infants Have a Higher Fat Mass Percentage in Comparison to Very Preterm Infants at Term-Equivalent Age

Abstract: Background: Early nutritional support of preterm infants is important because it influences long-term health and development. Body composition has an influence on cardiovascular disease, metabolic syndrome, and neurocognitive outcome in the long term. Objective: To assess body composition in preterm infants <32 weeks of gestation at term-equivalent age and to analyze the influence of an optimized nutritional approach. Methods: This is a prespecified secondary outcome analysis of a prospective observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
4
15
0
Order By: Relevance
“…Our study cohort had a relatively low incidence of postnatal growth restriction and a relatively high mean fat mass percentage. Others previously showed that preterm infants with postnatal growth restriction (weight SD at term age < −2 SD), had a lower fat mass percentage compared with preterm infants without postnatal growth restriction [ 17 , 18 ]. This could partially explain the higher fat mass percentage in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Our study cohort had a relatively low incidence of postnatal growth restriction and a relatively high mean fat mass percentage. Others previously showed that preterm infants with postnatal growth restriction (weight SD at term age < −2 SD), had a lower fat mass percentage compared with preterm infants without postnatal growth restriction [ 17 , 18 ]. This could partially explain the higher fat mass percentage in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Following this hypothesis, infants born preterm would simply start this transition “earlier” but at a comparable postnatal age as infants born at term 11 . Two studies comparing infants born “late” and “early” preterm indeed showed that infants born "early" preterm had a higher %FM around 32 to 36 weeks GA and at term equivalent age than infants born “later” preterm 44,45 . In addition to early adaptation, differences in nutrition and early feeding practices between term infants (“natural” ad lib oral feeding) and preterm infants (“artificial” parenteral and tube feeding) will likely play a role in the altered fat trajectory and earlier fat peak seen in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we hypothesize that in infants fed target fortified HM, adequate linear and head growth velocities will be achieved [ 37 , 38 ], and adiposity at term-equivalent age will be more similar to that of term-equivalent-age infants [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The current literature indicates that extremely and very preterm infants at term-equivalent age have a lower fat-free mass (FFM) and a greater fat mass percentage (FM%), compared with term-equivalent-age infants [ 28 , 29 ]. Reference values for body composition have been described for preterm infants [ 30 , 31 ], but the optimal body composition evolution in those infants remains to be determined.…”
Section: Introductionmentioning
confidence: 99%